Clofarabine for the treatment of adult acute lymphoid leukemia: the Group for Research on Adult Acute Lymphoblastic Leukemia intergroup. Issue 4 (April 2015) - Huguet, Françoise; Leguay, Thibaut; Raffoux, Emmanuel; Rousselot, Philippe; Vey, Norbert; Pigneux, Arnaud; Ifrah, Norbert; Dombret, Hervé
Abstract Clofarabine, a second-generation purine analog displaying potent inhibition of DNA synthesis and favorable pharmacologic profile, is approved for the treatment of acute lymphoblastic leukemia (ALL) after failure of at least two previous regimens in patients up to 21 years of age at diagnosis. Good neurologic tolerance, synergy with alkylating agents, management guidelines defined through pediatric ALL and adult acute myeloid leukemia, have also prompted its administration in more than 100 adults with Philadelphia chromosome-positive and negative B lineage and T lineage ALL, as single agent (40 mg/m2/ day for 5 days), or in combination. In a Group for Research on Adult Acute Lympho- blastic Leukemia (GRAALL) retrospective study of two regimens (clofarabine ± cyclophosphamide + / − etoposide (ENDEVOL) ± mitoxantrone ± asparaginase ± dexamethasone (VANDEVOL)), remission was achieved in 50% of 55 relapsed/refractory patients, and 17–35% could proceed to allogeneic stem cell. Clofarabine warrants further exploration in advanced ALL treatment and bridge-to-transplant.